REFLECTION OF WORLD LITERARY STYLES - Kairat Anarbaevich Mambetaliev (Galaxy International Interdisciplinary Research Journal, 2023)
The article talks about the foundation stone of world poetry going back to the ancient Greek culture, the reflection of world literary styles is considered.